Differential and difference equations with applications : contributions from the international conference on differential & difference equations and applications - Chipot, Michel; Dosla, Zuzana; Pinelas, Sandra (Springer Proceedings in Mathematics & Statistics, 2013)
The volume contains carefully selected papers presented at the International Conference on Differential & Difference Equations and Applications held in Ponta Delgada - Azores, from July 4-8, 2011 in honor of Professor Ravi P. Agarwal. The objective of the gathering was to bring together researchers in the fields of differential & difference equations and to promote the exchange of ideas and research. The papers cover all areas of differential and difference equations with a special emphasis on applications.